2008
DOI: 10.1111/j.1445-2197.2008.04722.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Tonsillectomy With Thermal Welding and the Conventional ‘Cold’ Tonsillectomy Technique

Abstract: When we compared TWS with the conventional 'cold' dissection tonsillectomy, we found that TWS tonsillectomy offered an innovative new tonsillectomy method with significantly reduced blood loss and reduced surgical time and without any increase in the postoperative pain. It was a useful method for tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 14 publications
(19 reference statements)
5
22
0
Order By: Relevance
“…The ideal technique should be fast, reliable, with less bleeding and pain and with quick recovery period. Although cold dissection tonsillectomy is the most common technique in surgical techniques, bipolar electro dissection tonsillectomy techniques are among alternates (Sezen et al, 2008). Though operative time and blood loss has been decreased with electro cautery technique, postoperative pain is a significant cause of morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal technique should be fast, reliable, with less bleeding and pain and with quick recovery period. Although cold dissection tonsillectomy is the most common technique in surgical techniques, bipolar electro dissection tonsillectomy techniques are among alternates (Sezen et al, 2008). Though operative time and blood loss has been decreased with electro cautery technique, postoperative pain is a significant cause of morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Sezen et al (2008) on 50 patients, the use of thermal welding has been found to significantly reduce operation time compared to cold technique method. In the study by Ozkiris et al (2013), it was found to be significantly longer in cold technique patients compared to thermal welding and bipolar cautery.…”
Section: Discussionmentioning
confidence: 99%
“…The [42] 81 bip. NS 0 4.9 2.5 2.5 0 VSS -thermal welding Sezen et al [43] 81 cold NS 0 0 ? 0 0 VSS -thermal welding Stavroulaki et al [44] 16 cold NS 0 ?…”
Section: Surgical Technique: Other Methodsmentioning
confidence: 99%
“…As postoperative pain is the most significant subjective symptoms as far as patients usually alert about it. (15) Many literatures mentioned that postoperative pain should be minimized not only for the patients comfort but also the pain usually impair swallowing with a great risk of dehydration, infection and secondary hemorrhage. (16) Generally in the present study, we found that postoperative pain score in the laser group was slightly greater in CO 2 laser tonsillectomy group with no statistical significant difference and this observation came in agreement to data of Auf et al 1997 who reported that laser tonsillectomy caused more postoperative pain than conventional blunt dissection.…”
Section: Discussionmentioning
confidence: 99%